Behavior and profile of high-speed internet broadband users - Wan Jusoh, Wan Jamaliah (2012)
High speed Internet access (Broadband) is a new technology introduces by service providers to the Malaysian consumers. This study was conducted in order to identify consumers’ behavior when using a high speed Internet as well as user’s satisfaction towards the services provided by the service providers. The study was conducted mainly for the Broadband users who lived within the Klang Valley. Based on the study findings, most users would prefer to use high speed Internet access or Broadband rather than the dial-up connectivity services. Most users would rather go for the speed than the price as Broadband users had the capability to conveniently browse through the Internet to retrieve information much faster. It is concluded that price does not influence people to use Broadband but speed and services offered were the main reasons for the users to turn to Broadband services. Overall findings showed that users were also satisfied with the services that they obtained from Broadband connectivity.